HAK DAN KEWAJIBAN KURATOR PASCA PUTUSAN PEMBATALAN PAILIT PADA TINGKAT KASASI OLEH MAHKAMAH AGUNG (STUDI KASUS KEPAILITAN PT. TELKOMSEL VS PT. PRIMA JAYA INFORMATIKA) - Sukses M. P. Siburian; Sunarmi Sunarmi; Utary Maharany Barus; Jelly Leviza (USU LAW JOURNAL, 2015)
ABSTRACT The Ruling of the Supreme Court on the case of PT. Telkomsel, the Supreme Court does not specify the compensation for the curator, whereas it has stipulated by the panel of judges of the Supreme Court. The objective of the research was to answer the problems about the right and obligation of a curator, the regulation on the compensation for a curator, and the right and obligation of a curator after the Ruling on the cancelation of bankruptcy in the cassation level by the Supreme Court on the case of PT. Telkomsel vs. PT. Prima Jaya Informatika was stipulated. Curator’s task is to manage and/or to settle bankruptcy property, while his right is to get compensation for his service through a judge’s verdict. According to UUKPKPU, the compensation for a curator’s service is charged to the petitioner and the debtor of the bankruptcy; but, according to Kepmen No. M.09-HT.05.10/1998, it is charged to a debtor. According to Permenkumham No. 1/2013, it is charged to the petitioner of the bankruptcy.  After the ruling on the cancellation of bankruptcy in the cassation level on the case of PT. Telkomsel is specified, the obligation of the curator was to announce the ruling in the cassation in the news of the Republic of Indonesia, at least in two daily newspapers. Under the law, a curator’s right should be specified in a judge’s verdict; but, in reality it is not stipulated in the Supreme Court’s Ruling. Keywords: Right, Obligation, Curator, Bankruptcy